Influence of Fat-Soluble Vitamin Intramuscular Supplementation on Kinematic and Morphometric Sperm Parameters of Boar Ejaculates - Calderón-Calderón, Josué; Sevilla, Francisco; Roldan, Eduardo R. S.; Barquero, Vinicio; Valverde, Anthony (Frontiers in Veterinary Science, 2022)
Ejaculate quality can be regarded as multifactorial, with nutrition being a factor that could directly influence sperm parameters. The present study aimed to evaluate seminal quality associated with seasonal fat-soluble vitamin supplementation of boars. Seven sexually mature boars were were randomly allotted to one of three groups, and fed one of three supplementary diets for 32 weeks: (1) control treatment (COD), without supplementation of fat-soluble vitamins, (2) treatment containing 100% fat-soluble vitamin supplementation administered intramuscularly, which was based on fat soluble vitamin supplementation (A, D3, E) (FVD1), and (3) treatment containing 50 % of fat-soluble vitamin supplementation (FVD½). Semen was collected at 7-day intervals. Semen samples were analyzed to assess several sperm parameters using the Computer-Assisted Semen Analysis (CASA) ISAS®v1 system. Results showed that groups receiving FVD1 and FVD½ supplementation had an increased semen volume. The percentages of motile and progressively motile sperm were increased by FVD1 treatment. A statistically significant interaction between treatment and season was found on percentage of motility and progressive motility (P<0.05). Sperm concentrations showed significant differences (P < 0.05) between treatments. Velocity variables (VSL, VCL and VAP) were higher (P < 0.05) in boars that received fat-soluble vitamin supplementation in comparison to controls receiving no supplementation. The FVD1 treatment presented spermatozoa with greater head size and more elongated heads (P < 0.05). Overall, the utilization of dietary fat-soluble vitamin supplementation significantly improved the semen quality of boar ejaculates. This highlights the importance of fat-soluble vitamin supplementation in sexually active boars.